Cognitive Behavioural Therapy for Anxiety Disorders in Young Children: A Dutch Open Trial of the Fun FRIENDS Program. Issue 1 (30th April 2020) - van der Mheen, Malindi; Legerstee, Jeroen S.; Dieleman, Gwendolyn C.; Hillegers, Manon H.J.; Utens, Elisabeth M.W.J.
Abstract: Anxiety disorders in young children are highly prevalent and increase the risk of social, school, and familial problems, and also of psychiatric disorders in adolescence and adulthood. Nevertheless, effective interventions for this age group are lacking. One of the few available interventions is the Fun FRIENDS program. We examined whether young children with anxiety disorders showed less anxiety after participating in Fun FRIENDS. Twenty-eight clinically anxious children (4–8 years old) participated in the cognitive behavioural Fun FRIENDS program. The program consists of 12 weekly 1.5-hour sessions and was provided in groups of 3 to 5 children. At preintervention and direct postintervention, parents completed the Anxiety Disorders Interview Schedule for Children and Child Behavior Checklist. Clinically and statistically significant decreases were found in number of anxiety disorders, symptom interference, emotional and behavioural problems, internalising problems, and anxiety problems. The decrease in anxious/depressed problems and externalising problems was not significant. Furthermore, higher preintervention anxiety levels predicted more treatment progress, whereas sex and age did not. The Dutch version of Fun FRIENDS is promising in treating anxiety disorders in young children. Randomised controlled trials are needed to draw definite conclusions on the effectiveness of Fun FRIENDS in a clinical setting.